Knowledge of Cervical Cancer Screening among Women across Different Socio-Economic Regions of China. - Jiangli Di; Shannon Rutherford; Jiuling Wu; Bo Song; Lan Ma; Jingyi Chen; Cordia Chu (PLoS ONE, 2015)
Background and objective China has a high burden of cervical cancer (CC) and wide disparities in CC burden exist among different socio-economic regions. In order to reduce these disparities, China's government launched the National Cervical Cancer Screening Program in Rural Areas (NCCSPRA) in 2009. Understanding the factors associated with underutilization of CC screening among target populations is important to improve the screening participation rate, and a high participation rate is key to achieving the goals of a screening program. However, data on the knowledge of CC among target populations in program areas is lacking in China. This study will investigate the knowledge of CC prevention and control among women in specific project counties to develop a better understanding of factors that might influence CC screening participation in order to improve the implementation of the NCCSPRA. Materials and methods A cross-sectional survey was conducted and face-to-face interview questionnaires were completed by 308 women who received CC screening services in 6 project counties of NCCSPRA across different socio-economic regions of China. ANOVA and Chi-square tests were used to compare the knowledge rates and scores across the different subgroups. Logistic regression was conducted to examine factors associated with knowledge level. Results The overall CC knowledge rate of the target population was only 19.5%. Regional socio-economic level, advice from doctors, age, and educational status were strong predictors of knowledge level of CC screening. Significantly lower knowledge rates and scores were identified in older women (55-64 years old), less educated women (with primary school or illiterate), women in less developed regions and women who did not receive any advice about screening results from doctors. Conclusion The knowledge of CC screening among women in the project counties of NCCSPRA was found to be very poor. Given the importance of knowledge in encouraging women to participate in screening is key to reducing CC burden in rural women in China, it is urgent that a targeted health promotion intervention is developed and implemented in project counties, especially targeting older women, women with less education and women in less developed regions, and focus on improving their CC knowledge and encouraging them to communicate with health care providers. The health promotion intervention targeting health care providers is also important to improve their knowledge of CC and provide best advice to women.